Method for manufacturing solid battery
By employing resin current collectors and intermediate layers with mixed components, the method addresses warping issues in solid-state battery manufacturing, ensuring stable ion and electron conduction paths and improved battery performance.
Patent Information
- Application Number
- JP2023110342
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
AI Technical Summary
Conventional solid-state battery manufacturing methods using ceramic or metal foils as current collectors result in warping and peeling during the pressing process, leading to disrupted ion and electron conduction paths and reduced capacity retention.
The method involves using resin current collectors with compressive strengths of 400 MPa or less, interspersing intermediate layers with mixed components, and pressing the electrode body precursor to suppress warping and peeling.
This approach effectively prevents warping and peeling during manufacturing, maintaining the integrity of ion and electron conduction paths, thereby enhancing battery performance.
Smart Images

Figure 2025008300000001 
Figure 2025008300000002 
Figure 2025008300000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing a solid-state battery. [Background technology]
[0002] 2. Description of the Related Art In recent years, secondary batteries such as lithium-ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), among others.
[0003] Secondary batteries use electrolytes that contain flammable organic solvents, so they require the installation of safety devices to suppress temperature rises in the event of a short circuit, as well as improvements to the structure and materials to prevent short circuits. In contrast, solid-state batteries, which use solid electrolyte layers to solidify the materials, do not use flammable organic solvents inside the battery, so safety devices can be simplified and they are thought to be superior in terms of manufacturing costs and productivity. As a conventional method for manufacturing a solid-state battery, a method has been proposed in which the battery components are laminated in advance in the order of the battery configuration, such as a positive electrode current collector / positive electrode active material layer / solid electrolyte layer / negative electrode active material layer / negative electrode current collector, and then pressed together to manufacture the battery (e.g., Patent Document 1). Conventional solid-state battery current collectors have a single-layer structure made of ceramic foil or metal foil, or a laminate containing ceramic foil and metal foil. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-125872 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, as described above, in the conventional manufacturing method of a solid-state battery, since a ceramic foil or a metal foil is used as a current collector, the current collector tends to stretch in the planar direction due to a pressing process during manufacturing. As a result, when a solid-state battery is manufactured, the current collector may locally warp and peel off from the active material layer. In the warped portion, the ion conduction path and the electron conduction path are likely to be cut, and the capacity retention rate is likely to be low. In view of the above circumstances, the present disclosure aims to provide a manufacturing method of a solid-state battery that suppresses warping during manufacturing. [Means for solving the problem]
[0006] Means for solving the above problems include the following means. <1> 1. A method for manufacturing a solid-state battery, comprising: pressing an electrode assembly precursor obtained by stacking a first laminate obtained by stacking a first resin current collector, a first active material layer, and a first solid electrolyte layer in this order, and a second laminate obtained by stacking a second resin current collector, a second active material layer, and a second solid electrolyte layer in this order, such that the first solid electrolyte layer and the second solid electrolyte layer are in contact with each other face-to-face. <2> The first resin collector and the second resin collector have a compressive strength of 400 MPa or less. <1> A method for producing the solid-state battery according to claim 1. <3> The electrode body precursor is a first intermediate layer interposed between the first resin current collector and the first active material layer, the first intermediate layer including at least one component contained in the first active material layer and at least one component contained in the first resin current collector; a second intermediate layer interposed between the second resin current collector and the second active material layer, the second intermediate layer including at least one component contained in the second active material layer and at least one component contained in the second resin current collector. <1> or <2> A method for producing the solid-state battery according to claim 1. Effect of the Invention
[0007] According to the present disclosure, there is provided a method for manufacturing a solid-state battery that suppresses warping during manufacturing. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a solid state battery according to the present disclosure. [Diagram 2] FIG. 2 is an example of a schematic cross-sectional view in the stacking direction of the solid-state battery of the present disclosure. [Diagram 3] FIG. 3 is a graph showing the relationship between the battery voltage and the discharge capacity in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment that is an example of the present disclosure will be described. These descriptions and examples are intended to illustrate the embodiment, and are not intended to limit the scope of the present disclosure.
[0010] In the present disclosure, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In the present disclosure, in the ranges of numerical values described stepwise, the upper limit or lower limit of one numerical range may be replaced with the upper limit or lower limit of another numerical range of numerical values described stepwise. In addition, in the ranges of numerical values described in the present disclosure, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. In the present disclosure, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In this disclosure, the term "layer" includes cases where the layer is formed over the entire area when the area in which the layer exists is observed, as well as cases where the layer is formed over only a portion of the area. In the present disclosure, the term "step" refers not only to an independent step, but also to a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.
[0011] -Solid-state battery manufacturing method- A method for producing a solid state battery according to the present disclosure includes a step of pressing an electrode body precursor obtained by stacking a first laminate obtained by stacking a first resin current collector, a first active material layer, and a first solid electrolyte layer in this order, and a second laminate obtained by stacking a second resin current collector, a second active material layer, and a second solid electrolyte layer in this order, such that the first solid electrolyte layer and the second solid electrolyte layer are in contact with each other face to face.
[0012] In the manufacturing method of the solid-state battery according to the present disclosure, the current collector is a resin current collector. Therefore, when the first laminate and the second laminate are laminated so that the solid electrolyte layers of both are in contact with each other and pressed, the elongation in the planar direction caused by the pressing pressure applied in the thickness direction of the current collector is suppressed. As a result, warping during manufacturing is suppressed. In other words, warping of the current collector is suppressed, and peeling of the current collector from the active material layer is suppressed, so that the deterioration of the battery performance due to warping is also suppressed.
[0013] The solid-state battery of the present disclosure includes a so-called all-solid-state battery using a solid electrolyte as an electrolyte, and the solid electrolyte may contain an electrolytic solution in an amount of less than 10 mass% based on the total amount of the electrolyte. The solid electrolyte may be a composite solid electrolyte containing an inorganic solid electrolyte and a polymer electrolyte.
[0014] An example of the solid-state battery of the present disclosure will be described with reference to the drawings. FIG. 1 is a schematic cross-sectional view showing an example of the solid-state battery of the present disclosure. The solid-state battery shown in FIG. 1 includes an anode including an anode current collector 113 (first resin current collector) and an anode active material layer A (first active material layer), a solid electrolyte layer B, and a cathode including a cathode current collector 115 (second resin current collector) and a cathode active material layer C (second active material layer). In FIG. 1, the solid electrolyte layer B has a two-layer structure including a first solid electrolyte layer 20 and a second solid electrolyte layer 30. The anode active material layer A includes an anode active material 101, a conductive assistant 105, a binder 109, and a solid electrolyte 102. The cathode active material layer C includes a cathode active material 103, a conductive assistant 107, a binder 111, and a solid electrolyte 102.
[0015] An example of the laminated structure of the solid-state battery of the present disclosure will be described with reference to the drawings. FIG. 2 is an example of a schematic cross-sectional view of the laminated direction of the solid-state battery of the present disclosure. The solid-state battery shown in FIG. 2 is a laminated body in which a negative electrode current collector 113 (first resin current collector), a negative electrode active material layer A (first active material layer), a first solid electrolyte layer 20, a second solid electrolyte layer 30, a positive electrode active material layer C (second active material layer), and a positive electrode current collector 115 (second resin current collector) are laminated in this order. In FIG. 2, the solid electrolyte layer B has a two-layer structure of the first solid electrolyte layer 20 and the second solid electrolyte layer 30. Although not shown, the solid state battery of the present disclosure may further include a first intermediate layer between the negative electrode current collector 113 (first resin current collector) and the negative electrode active material layer A (first active material layer). Although not shown, the solid state battery of the present disclosure may further include a second intermediate layer between the positive electrode active material layer C (second active material layer) and the positive electrode current collector 115 (second resin current collector).
[0016] When a set of a positive electrode, a solid electrolyte layer, and a negative electrode is defined as a power generation unit, the solid-state battery may have only one power generation unit or may have two or more power generation units. When the solid-state battery has two or more power generation units, the power generation units may be connected in series or in parallel.
[0017] When the solid-state battery has two or more power generating units (i.e., when it is a stacked-type battery), at least one of the positive electrode or negative electrode has the configuration of the solid-state battery according to the present disclosure, i.e., the current collector is a resin current collector, and from the viewpoint of further suppressing warping, it is preferable that the current collectors in all of the power generating units are resin current collectors.
[0018] In the solid-state battery, the stacking end faces (i.e., side faces) of the stacking structure of the positive electrode / solid electrolyte layer / negative electrode may be sealed with a sealant such as resin. The negative electrode current collector 113 and the positive electrode current collector 115 may have a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer disposed on the outer circumferential surface. The shape of the solid-state battery is not particularly limited, and may be, for example, a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type.
[0019] Hereinafter, matters common to both the first resin current collector and the second resin current collector will be collectively referred to simply as "resin current collector." The first resin current collector and the second resin current collector may have the same or different component compositions. For example, when the type and amount of resin contained in the material, the type and amount of conductive material contained in the material, etc. are different, the first resin current collector and the second resin current collector are considered to have different component compositions. Hereinafter, matters common to both the first active material layer and the second active material layer will be collectively referred to simply as "active material layer". The first active material layer and the second active material layer may have the same or different component compositions. For example, when the type and amount of active material contained in the material, the type and amount of binder, etc. are different, the first active material layer and the second active material layer are considered to have different component compositions. Hereinafter, matters common to both the first solid electrolyte layer and the second solid electrolyte layer will be collectively referred to simply as "solid electrolyte layer". The first solid electrolyte layer and the second solid electrolyte layer may have the same or different component compositions. For example, when the type and amount of electrolyte are different, the first solid electrolyte layer and the second solid electrolyte layer are considered to have different component compositions.
[0020] Each layer structure will be described in detail below.
[0021] [Resin current collector] The resin collector may be any resin molded body having electrical conductivity, and may be, for example, a molded body having no electrical conductive material and containing a conductive polymer, or a molded body having a resin and a conductive material. Here, "having electrical conductivity" means that the electrical conductivity is 5.0 mS / cm or more.
[0022] Examples of the resin include known thermoplastic resins such as poly(meth)acrylic acid, polymethyl(meth)acrylate, polyethylene, polypropylene, polyethylene terephthalate, polyether nitrile, polyimide, polyamide, polytetrafluoroethylene, polyacrylonitrile, poly(meth)acrylate, and halogenated vinyl resin; thermosetting resins such as epoxy resin, vinyl ester resin, unsaturated polyester resin, phenol resin, and melamine resin; and known conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, polyparaphenylene, polyphenylenevinylene, polyacrylonitrile, and polyoxadiazole. The resin may be used alone or in combination of two or more kinds. Among the above, from the viewpoint of further suppressing peeling of the active material layer from the resin current collector and deterioration of the cycle characteristics, the resin preferably contains at least one of a thermoplastic resin and a conductive polymer, more preferably contains a thermoplastic resin, and further preferably contains one type of resin selected from the group consisting of polymethyl(meth)acrylate, poly(meth)acrylic acid, and polyacrylonitrile.
[0023] In the present disclosure, the term "(meth)acrylic acid" refers to a concept that includes both acrylic acid and methacrylic acid, and the term "(meth)acrylate" refers to a concept that includes both acrylate and methacrylate.
[0024] The resin may be a crystalline resin, an amorphous resin, or a mixture of both, and from the viewpoint of further suppressing warping of the active material layer from the resin current collector, an amorphous resin is preferable. The "crystalline" resin refers to the presence of an endothermic peak with a half-width of 10°C or less when measured at a heating rate of 10 (°C / min) in differential scanning calorimetry (DSC measurement). On the other hand, the "amorphous" resin refers to the half-width exceeding 10°C, or the absence of a clear endothermic peak.
[0025] The softening temperature of the resin varies depending on the type of resin, but from the viewpoint of the strength of the resin current collector and the suppression of deterioration of the active material, the softening temperature of the resin is preferably equal to or lower than the crystallization temperature of the solid electrolyte contained in the solid electrolyte layer described later. The softening temperature of the resin is determined from a DSC curve obtained by differential scanning calorimetry (DSC).
[0026] Examples of the conductive material include carbon materials, conductive polymers, and metal particles. Examples of carbon materials include particulate carbon materials, fibrous carbon materials, etc. Examples of particulate carbon materials include graphite, acetylene black (AB), Ketjen black (KB), etc. Examples of fibrous carbon materials include carbon nanotubes (CNT), carbon nanofibers (CNF), vapor grown carbon fibers (VGCF), etc. Examples of the conductive polymer include polythiophene, polyacetylene, polyparaphenylene, and polyisothianaphthene. Metal particles include nickel, copper, iron, stainless steel, and the like particles. Among the above, the conductive material preferably contains at least one of a carbon material and a fibrous carbon material, and more preferably contains at least one of acetylene black (AB) and vapor grown carbon fiber (VGCF).
[0027] From the viewpoint of further suppressing warping, the content of the conductive material is preferably from 10% by mass to 50% by mass, more preferably from 15% by mass to 43% by mass, and even more preferably from 15% by mass to 35% by mass, relative to the total solid content of the resin collector.
[0028] The resin collector may further contain other materials in addition to the resin and the conductive material, such as a binder, a dispersant that improves the dispersibility of the conductive assistant in the slurry, and a wetting agent that improves the wettability of the foil and the slurry.
[0029] From the viewpoint of suppressing warping, the resin current collector should have a linear expansion coefficient of 100×10 -6 ppm / K or more 500×10 -6 It is preferable that the concentration is less than 230×10 ppm / K. -6 ppm / K or more 430×10 -6 More preferably, it is 200×10 ppm / K or less. -6 ppm / K or more 350×10 -6 It is more preferable that the coefficient of linear expansion is not more than ppm / K. The value of the linear expansion coefficient is a value measured by a method in accordance with JIS H7404-1993.
[0030] There are no particular limitations on the method for setting the linear expansion coefficient of the resin current collector within the above range, and examples thereof include a method in which the resin in the resin current collector is one of the above-mentioned suitable resins.
[0031] The thickness of the resin current collector is not particularly limited, but from the viewpoint of further suppressing warping, it is preferably 5 μm or more and 80 μm or less, more preferably 10 μm or more and 50 μm or less, and even more preferably 10 μm or more and 30 μm or less.
[0032] The thickness of the resin current collector was determined by observing a cross section of the resin current collector cut in the thickness direction using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX) and measuring the thickness at any ten points, and averaging the thicknesses.
[0033] The method for forming the resin current collector is not particularly limited, and examples thereof include a method in which, when the resin is thermoplastic, a coating liquid containing the resin and a conductive material is applied, dried, and molded; and, when the resin is thermosetting, a method in which raw materials such as a resin precursor or a monomer and a conductive material are placed in a mold and heated to solidify.
[0034] From the viewpoint of further suppressing warping, the resin current collectors, i.e., the first resin current collector and the second resin current collector, preferably have a compressive strength of 450 MPa or less, more preferably 400 MPa or less, and even more preferably 100 MPa or more and 400 MPa or less. The compressive strength of a resin current collector is determined as follows. A test specimen is prepared by stacking multiple resin current collectors. When this test specimen is compressed in a uniaxial press, the compressive strength at which plastic deformation begins (i.e., 5% deformation) is taken as the compressive strength. If the test specimen breaks before 5% deformation, the maximum strength until breakage is taken as the compressive strength.
[0035] [Active material layer] The active material layer contains an active material. The type of active material is not particularly limited, and known materials for the negative electrode and the positive electrode can be used.
[0036] The active material layer may further contain a solid electrolyte, a binder, and the like in addition to the active material, as necessary.
[0037] The thickness of the active material layer is not particularly limited, but from the viewpoint of, for example, achieving better charge / discharge characteristics and further suppressing warping of the first resin current collector from the first active material layer, it is preferably 0.1 μm or more and 100.0 μm or less, preferably 1.0 μm or more and 100.0 μm or less, and more preferably 30.0 μm or more and 100.0 μm or less.
[0038] The thickness of the active material layer is the average value of thicknesses measured at any ten points on a cross section of the active material layer cut in the thickness direction using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX).
[0039] [Solid electrolyte layer] The solid electrolyte layer contains a solid electrolyte. From the viewpoint of battery performance, the solid electrolyte preferably contains at least one solid electrolyte species selected from the group of solid electrolytes consisting of sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes, and more preferably contains a sulfide solid electrolyte. As a sulfide solid electrolyte, it is preferable to contain sulfur (S) as the main component of the anion element, and in addition to S, it is also preferable to contain, for example, Li element and A element. The A element is at least one selected from the group consisting of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In. The sulfide solid electrolyte may further contain at least one of O and halogen elements. Examples of the halogen element (X) include F, Cl, Br, I, etc. The composition of the sulfide solid electrolyte is not particularly limited, and examples include xLi2S·(100 - x)P2S5 (70 ≤ x ≤ 80), yLiI·zLiBr·(100 - y - z)(xLi2S·(1 - x)P2S5) (0.7 ≤ x ≤ 0.8, 0 ≤ y ≤ 30, 0 ≤ z ≤ 30). The sulfide solid electrolyte may have a composition represented by the following general formula (1). Li 4-x Ge 1-x P x S4(0 < x < 1) ··· Formula (1) In Formula (1), at least a part of Ge may be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. Also, at least a part of P may be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. A part of Li may be substituted with at least one selected from the group consisting of Na, K, Mg, Ca, and Zn. A part of S may be substituted with a halogen. The halogen is at least one of F, Cl, Br, and I. As an oxide solid electrolyte, it is preferable to contain oxygen (O) as the main component of the anion element, and for example, it may contain Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Examples of the oxide solid electrolyte include garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, Li-P-O-based solid electrolytes, Li-B-O-based solid electrolytes, etc. Examples of the garnet-type solid electrolyte include, for example, Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x )O12 (0 ≦ x ≦ 2), Li5La3Nb2O 12 Examples include the like. Examples of perovskite-type solid electrolytes include, for example, (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. Examples of NASICON-type solid electrolytes include, for example, Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. Examples of Li-P-O-based solid electrolytes include Li3PO4, LIPON (a compound in which part of the O in Li3PO4 is replaced by N), and examples of Li-B-O-based solid electrolytes include Li3BO3 and a compound in which part of the O in Li3BO3 is replaced by C, etc. As the halide solid electrolyte, a solid electrolyte containing Li, M, and X (M represents at least one of Ti, Al, and Y, and X represents F, Cl, or Br) is suitable. Specifically, Li 6-3z Y z X6 (X represents Cl or Br, and z satisfies 0 < z < 2), Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≦ 1.5) is preferred. Among Li 6-3z Y z X6, Li3YX6 (X represents Cl or Br) is more preferred in terms of excellent lithium ion conductivity, and further, Li3YCl6 is preferred. Also, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≦ 1.5) is preferably included together with a solid electrolyte such as a sulfide solid electrolyte, from the viewpoint of, for example, suppressing the oxidative decomposition of the sulfide solid electrolyte.
[0040] The crystallization temperature of the solid electrolyte varies depending on the type of solid electrolyte employed, but for example, it is preferably 0% or more and 90% or less, more preferably 20% or more and 85% or less, and even more preferably 50% or more and 85% or less. Note that the crystallinity of the solid electrolyte is a value measured by the X-ray diffraction method.
[0041] 〔Intermediate layer〕 The electrode body precursor may further have a first intermediate layer interposed between the first resin current collector and the first active material layer, in which at least one component contained in the first active material layer and at least one component contained in the first resin current collector are mixed. The electrode body precursor may further have a second intermediate layer interposed between the second resin current collector and the second active material layer, the second intermediate layer including at least one component contained in the second active material layer and at least one component contained in the second resin current collector. When the electrode body precursor has an intermediate layer, the adhesion between the active material layer and the resin current collector is improved, and warping during production is further reduced.
[0042] Hereinafter, matters common to both the first intermediate layer and the second intermediate layer will be collectively referred to simply as "intermediate layer."
[0043] From the viewpoint of enhancing the anchor effect and further reducing warpage, the intermediate layer is preferably a layer in which at least the active material contained in the active material layer and the resin contained in the resin current collector are mixed.
[0044] From the viewpoint of enhancing the anchor effect and further reducing warping, the thickness of the intermediate layer relative to the thickness of the resin current collector (intermediate layer / resin current collector) is preferably 1 / 30 or more and 1 / 4 or less, more preferably 1 / 20 or more and 1 / 5 or less, and even more preferably 1 / 10 or more and 1 / 6 or less.
[0045] The thickness of the intermediate layer is not particularly limited, but from the viewpoint of, for example, achieving better charge / discharge characteristics, enhancing the anchor effect, and further reducing warping, it is preferably 0.1 μm or more and 15.0 μm or less, more preferably 0.4 μm or more and 10.0 μm or less, and even more preferably 0.6 μm or more and 8.0 μm or less.
[0046] The thickness of the intermediate layer is determined by observing a cross section of the intermediate layer cut in the thickness direction using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX) and averaging the thicknesses measured at any ten points. The components contained in the intermediate layer can be confirmed by EDX analysis of the chemical composition of a laminate cross section cut in the thickness direction of the intermediate layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX).
[0047] The method for forming the intermediate layer is not particularly limited, and examples thereof include: 1) when the resin in the resin current collector is thermoplastic, a method including a step of heating a laminate in which the resin current collector and the active material layer are laminated to a temperature equal to or higher than the softening temperature of the resin, and pressing the laminate; and 2) when the resin in the resin current collector is thermosetting, a method of filling a precursor of a thermosetting resin and components such as the active material and binder in the active material layer into a mold and molding by heating, etc.
[0048] In the method for producing a solid-state battery according to the present disclosure, a first laminate obtained by laminating a first resin current collector, a first active material layer, and a first solid electrolyte layer in this order, and a second laminate obtained by laminating a second resin current collector, a second active material layer, and a second solid electrolyte layer in this order, are obtained by laminating the first solid electrolyte layer and the second solid electrolyte layer in this order, such that the first solid electrolyte layer and the second solid electrolyte layer are in contact with each other face to face. The first solid electrolyte layer and the second solid electrolyte layer can be laminated by a known method for laminating solid-state batteries.
[0049] In the method for producing a solid-state battery according to the present disclosure, the electrode body precursor is pressed. Examples of the pressing method include roll pressing, cold isostatic pressing (CIP), hydrostatic pressing, and uniaxial pressing. The pressing pressure is not particularly limited, but is, for example, preferably 450 MPa or less, more preferably 400 MPa or less, and further preferably 300 MPa or more and 400 MPa or less.
[0050] The manufacturing method of the solid-state battery of the present disclosure may further include other steps other than the pressing step, such as a step of initially charging the solid-state battery, a step of converting the solid-state battery into a bipolar solid-state battery, a step of processing the solid-state battery into a predetermined size by cutting, milling, punching, or the like, and a step of stacking single-cell solid-state batteries. EXAMPLES
[0051] <Example 1> A slurry containing a sulfide-based solid electrolyte (SE; Li2S-P2S5), an acrylonitrile butadiene rubber (ABR)-based binder, heptane, and butyl butyrate was dispersed using an ultrasonic dispersion device to obtain an SE slurry. The mass ratio of the SE to the ABR-based binder (SE:ABR-based binder) was adjusted to 99.4:0.6. This SE slurry was applied onto a stainless steel (SUS) foil by the blade method, dried on a hot plate at 50°C for 1 minute, and further dried on a hot plate at 150°C for 30 minutes to obtain an SE layer, which is a second solid electrolyte layer. NCA-based positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 A slurry containing NCA, a sulfide-based solid electrolyte (SE; Li2S-P2S5), vapor grown carbon fiber (VGCF), a polyvinylidene fluoride (pVdF)-based binder, and butyl butyrate was stirred with an ultrasonic diffusion device to obtain a positive electrode slurry. Here, the mass ratio of NCA, SE, VGCF, and PVdF-based binder (NCA:SE:VGCF:PVdF-based binder) was adjusted to 84.7:13.4:1.3:0.6. This positive electrode slurry was applied onto the SE layer by the blade method, dried on a hot plate at 50 ° C for 20 minutes, and further dried on a hot plate at 150 ° C for 30 minutes to obtain a positive electrode active material layer, which is a second active material layer. A resin slurry, which was a mixture of a resin, a conductive material, and a solvent, was applied onto the second active material layer by a blade method, and dried for 20 minutes on a hot plate at 50° C., and then further dried for 30 minutes on a hot plate at 150° C., to provide a second resin current collector on the second active material layer. The SUS foil was then peeled off to obtain a second laminate consisting of a second resin current collector / second intermediate layer / second active material layer / second solid electrolyte layer.
[0052] A slurry containing a sulfide-based solid electrolyte (SE; Li2S-P2S5), an acrylonitrile butadiene rubber (ABR)-based binder, heptane, and butyl butyrate was dispersed using an ultrasonic dispersion device to obtain an SE slurry. The mass ratio of the SE to the ABR-based binder (SE:ABR-based binder) was adjusted to 99.4:0.6. This SE slurry was applied onto a stainless steel (SUS) foil by the blade method, dried on a hot plate at 50°C for 1 minute, and further dried on a hot plate at 150°C for 30 minutes to obtain an SE layer, which is a first solid electrolyte layer. A negative electrode slurry was obtained by dispersing a slurry containing a negative electrode active material (graphite, a sulfide-based solid electrolyte (SE; Li2S-P2S5), a polyvinylidene fluoride (PVdF)-based binder, and butyl butyrate using an ultrasonic dispersion device. Here, the mass ratio of the graphite, SE, and PVdF-based binder (graphite:SE:PVdF-based binder) was adjusted to 58.2:39.0:2.8. This negative electrode slurry was applied onto the SE layer, which is the first solid electrolyte layer, by a blade method, dried on a hot plate at 50°C for 20 minutes, and further dried on a hot plate at 150°C for 30 minutes to obtain a negative electrode active material layer, which is the first active material layer. A resin slurry containing a mixture of resin (polymethyl methacrylate), conductive material (acetylene black) and a solvent was applied onto the first active material layer by a blade method, dried for 20 minutes on a hot plate at 50° C., and further dried for 30 minutes on a hot plate at 150° C. to provide a first resin current collector on the first active material layer. The SUS foil was then peeled off to obtain a first laminate consisting of the first resin current collector / first intermediate layer / first active material layer / first solid electrolyte layer.
[0053] The first and second laminates obtained above were brought into contact with each other so that the first solid electrolyte layer and the second solid electrolyte layer faced each other, and were bonded by a static pressure press at 392 MPa for 1 minute at 25°C to obtain a single-cell solid-state battery laminated in the order of "first resin collector / first intermediate layer / first active material layer / first solid electrolyte layer / second solid electrolyte layer / second active material layer / second intermediate layer / second resin collector" as shown in Figure 2. After three layers of single-cell solid-state batteries were laminated in series, aluminum foil and roughened copper foil were placed on the outermost layer, and the single-cell solid-state batteries were pressed from one side in the lamination direction by a uniaxial press at 20 MPa, 30 seconds, and 135°C to be bonded. Then, the four end sides of the solid-state battery were cut with a carbide blade to obtain a bipolar solid-state battery.
[0054] The thickness of the intermediate layer relative to the thickness of the resin current collector in the solid battery of Example 1 (intermediate layer / resin current collector) was 1 / 6. The thicknesses of the first intermediate layer and the second intermediate layer in the solid battery of Example 1 were 2.6 μm and 2.4 μm, respectively. The linear expansion coefficient of the resin current collector in the solid battery of Example 1 was 300×10 -6 It was ppm / K.
[0055] <Charge / discharge test> Using a charge / discharge device (manufactured by Toyo Systems Co., Ltd.), a charge / discharge test was carried out for two cycles under conditions of a voltage range of 9.0 V to 12.6 V, a current value of 0.522 mA, and a final current of 0.0522 mA.
[0056] Fig. 3 is a graph showing the relationship between the battery voltage and the discharge capacity in Example 1. As shown in Fig. 3, the solid-state battery in Example 1 had a suppressed fluctuation in energy loss accompanying charging and discharging. In other words, it was found that warping was suppressed. [Explanation of symbols]
[0057] 20 First solid electrolyte layer 30 Second solid electrolyte layer A Negative electrode active material layer (first active material layer) B Solid electrolyte layer C Positive electrode active material layer (second active material layer) 101 Negative electrode active material 102 Solid electrolyte 103 Cathode active material 105, 107 Conductive additives 109, 111 Binder 113 Negative electrode current collector (first resin current collector) 115 Positive electrode collector (second resin collector)
Claims
1. 1. A method for manufacturing a solid-state battery, comprising: pressing an electrode assembly precursor obtained by stacking a first laminate obtained by stacking a first resin current collector, a first active material layer, and a first solid electrolyte layer in this order, and a second laminate obtained by stacking a second resin current collector, a second active material layer, and a second solid electrolyte layer in this order, such that the first solid electrolyte layer and the second solid electrolyte layer are in contact with each other face-to-face.
2. The method for producing a solid-state battery according to claim 1 , wherein the first resin current collector and the second resin current collector have a compressive strength of 400 MPa or less.
3. The electrode body precursor is a first intermediate layer interposed between the first resin current collector and the first active material layer, the first intermediate layer including at least one component contained in the first active material layer and at least one component contained in the first resin current collector; 3. The method for producing a solid-state battery according to claim 1, further comprising: a second intermediate layer interposed between the second resin current collector and the second active material layer, the second intermediate layer including at least one component contained in the second active material layer and at least one component contained in the second resin current collector.
Citation Information
Patent Citations
Electrode for lithium ion secondary battery
JP2007059387A
Electrode and its manufacturing method
JP2010067581A
Method of manufacturing all-solid battery
JP2015118870A
Electrode and method of manufacturing the same
JP2017084507A
Electrode for lithium ion secondary battery and method for manufacturing the same
JP2017152383A